Hotchkiss: A Chronicle of an American School - Kolowrat, Ernest (Rowman & Littlefield Publishers, 1998)
How has the Hotchkiss School managed to accommodate a hundred years of unprecedented change—a century during which horse-and-buggy trails have become less familiar than the fiery trails of space-bound vehicles, and Victorian propriety has yielded to unabashed self-expression? The short answer—carefully; certainly not without considerable tension and the constant need to mediate between the forces of tradition and innovation. Oh yes, also by following the golden rule: do not disturb the cherished memories of alumni—and, more recently, of alumnae as well.